Investigating the Use of Density Polyethylene in Modifying Bitumen to Improve Performance of Flexible Pavements Along Climbing Lanes - Derrick Adriko (Uganda Christian University, 2024)
This study investigated the application of bitumen modification in improving the performance of flexible pavements against rutting along climbing lanes. Such sections are characterized as severely loaded sites that experience deceleration of traffic and increased loading time. As the pavement temperature increases, the binder softens and is unable to withstand the increased loading hence causing shear deformation. A case study was evaluated at the climbing lane section along Bweyogerere – Jinja road that experienced premature deformation a few years after its reconstruction. The study deduced that the failure was caused by instability rutting within the asphalt layer. The properties of both aggregates and bitumen were evaluated to understand the cause of failure. The study employed mechanistic – empirical approach where the index properties of the materials were related to pavement performance using recommended asphalt models. Whereas the aggregates were found to possess excellent performance, the bitumen was found to be temperature sensitive hence causing reduced stiffness at high temperatures. Bitumen modification with LLDPE showed reduction in temperature susceptibility and increased stiffness modulus at high service operating temperatures and loading time. Asphalt mix specimen with 2% LLDPE increased the resistance to permanent deformation without affecting pavement durability. The modified specimen were subjected to ITS and PRD tests where an increase in tensile strength of 16.7% was recorded. The air voids at refusal density increased by 42% signifying increased flexibility upon secondary compaction under heavy loads thereby increasing service time and solving the issue of premature deformation.